Silence, Sound, and Affect - Dominika Ferens (Res Rhetorica, 2020)
The present paper offers a subjective overview of approaches to affect. Research on affect accelerated in the last two decades within several disciplines, in response to different concerns and research questions, energized by new research in psychology and, more recently, neuroscience. But while affect studies scholars agree that emotions, amplified by the media, course through all social relations and electrify our entire bodies, scholars attracted to specific clusters of theories have little to say to each other. To remedy this situation, I attempt to bridge several seemingly incompatible strands of research on affects in psychology, cultural studies, and media studies, in order to bring out commonalities and patterns that may prove useful for reading literature and other cultural artifacts. Defining affects, I refer to the practice of tuning musical instruments to a specific pitch as an analogy for the way affects resonate from the macro to the micro levels of social life.